Development of High Blood Pressure Device based on Pulse Transit Time Measurement for Hypertension Disease - Hishamuddin, Muhamad Akmal Hafiz; Adon, Mohamad Nazib (Evolution in Electrical and Electronic Engineering, 2022)
High blood pressure, often known as hypertension, is a major health concern for people all over the world, including in Malaysia. Hypertensive individuals should visit their doctor for blood pressure monitoring on a regular basis, and some have complained that the arm cuff produces numbness all over their arm after numerous readings due to its pressure. As a result, this project was formed in order to address all of these issues. It used a Photoplethysmography (PPG) sensor with signal processing within the MATLAB R2020a program to monitor blood pressure using the Pulse Transit Time (PTT) method, and it was embedded with ThingSpeak and ThingView Internet of Things (IoT) applications. Blood pressure readings in systolic and diastolic pressure are displayed on a ThingSpeak webpage for a physician on a desktop computer and a ThingView application for an Android user in this project. Before and after 20 minutes of continuous exercise, the PPG signals of a healthy 23-year-old volunteer were measured ten times. The result shows that there is a link between PTT and blood pressure, with the standard error computed at 0.006 and growing proportionately in the presence of motion artifact, based on the regression equations constructed. Finally, this project is projected to be able to assess blood pressure in a remote monitoring system and develop Malaysian healthcare technology.